Evaluation of halal supply chain management’s performance in culinary enterprises - Vita Sarasi; Yunizar; Nugroho Djati Satmoko (Cogent Business & Management)
This research evaluates the effectiveness of Halal Supply Chain Management (HSCM) in Indonesia through a case study of the fast food chain d’BO. This study identifies inefficiencies and bottlenecks in the company’s supply chain and applies strategies to streamline operations and eliminate waste while maintaining overall performance. A mixed methods approach is employed, integrating quantitative methods such as Supply Chain Operation Reference (SCOR) for performance analysis, Analytical Hierarchy Process (AHP) and Objective Matrix (OMAX), and Traffic Light System (TLS) for monitoring performance. Additionally, the qualitative method Causal Loop Diagram (CLD) is used to analyze systemic interactions between performance indicator. The novelty lies in the innovative application of CLD for decision-making strategies and policies, along with the comprehensive mixed methods approach tailored specifically for the halal food sector. Results a ‘Fair’ supply chain performance rating of 5.975 out of 10. Improvements are needed in 32 KPIs, especially in inventory planning flexibility, production balance, and supplier communication. This research provides practical guidance for improving halal supply chain management, enhances operational performance, contributes to data-driven policy development, serves as a model for other fast food industries, and enriches the literature on halal supply chain management, particularly in the Indonesian context.